PENGEMBANGAN WEBSITE PADA MATERI KEANEKARAGAMAN HAYATI TNUK BERBASIS HASIL RISET UNTUK MENINGKATKAN LITERASI KONSERVASI SISWA SMP KELAS VII - Muhammad Raflia; Adi Nestiadi; Septi Kurniasih; Suroso Mukti Leksono (Jurnal Penelitian Pendidikan IPA, 2024)
This study was prompted by the lack of maximization of the use of learning media, especially the use of information and communication technology (ICT) based media, resulting in the lack of learning resources on biodiversity topics and the lack of understanding of conservation education among 7th grade students. The purpose of the research is the determination of the level of validity of the developed web site. Research and development adapted from Thiagarajan's development model was used as the method. The research tools used in this study were interviewing and validating sheets. The steps of exploring potentials and problems, data collection, product design, product validation and product revision were used to develop the website learning media. The results showed that the validity level of biodiversity research website material to improve conservation literacy among seventh graders was 89% with a very valid category, so it can be used for learning.